Electrocatalysis of Lithium (Poly-) Sulfides in Organic Ether-Based Electrolytes. Issue 16 (4th January 2021) - Ante, M. J.; Sörgel, Ş.; Opitz, M.; Freudenberger, R.; Bund, A.
Abstract : This work aims at identifying an effective electrocatalyst for polysulfide reactions to improve the electrode kinetics of the sulfur half-cell in liquid organic electrolytes for alkali-sulfur cells. To increase the charge and discharge rates and energy efficiency of the cell, functionalized electrocatalytic coatings have been prepared and their electrode kinetics have been measured. To the best of our knowledge, there is no extensive screening of electrocatalysts for the sulfur electrode in dimethoxyethane:1, 3-dioxolane (DME:DOL) electrolytes. In order to identify a suitable electrocatalyst, apparent exchange current densities at various materials (Al, Co, Cr, Cu, Fe, Steel, glassy carbon, ITO, Ni, Pt, Ti, TiN, Zn) are evaluated in a polysulfide electrolyte using potentiodynamic measurements with a Butler-Volmer fit. The chemical stability and surface morphology changes after electrochemical measurements are assessed with X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). The results show that cobalt is a promising candidate with appropriate electrocatalytic properties for polysulfide reactions while being stable in the electrochemical environment, followed by chromium in terms of catalytic activity and stability. Sputtered TiN was found to be a very stable material with very low catalytic activity, a possible current collector for the cell.